Tungsten wire surface cleaning using electropolishing process - Jurčík, M. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
This article deals with the preparation of tungsten wires surface for electrochemical etching process via electropolishing process. Cleaning of the wire surface is very important for obtaining field emission cold cathodes with sharp tips and low contamination on its surface which are made from these tungsten wires. There are many ways to clean wire surface such as heating it in a ultra vacuum, using solutions and acids, mechanical cleaning etc. Each of these methods has advantages and disadvantages and due to electropolishing process quickness this method was selected for futher usage.
Keywords: electropolishing; electrochemical cleaning; field emission cold cathode; tungsten